Traumatic shock and electroshock: the difficult relationship between anatomic pathology and psychiatry in the early 20th century - Patriarca, C.; Clerici, C.A. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2019)
In the conviction that a look at the past can contribute to a better understanding of the present in the field of science too, we discuss here two aspects of the relationship between early 20th century anatomic pathology and psychiatry that have received very little attention, in Italy at least. There was much debate between these two disciplines throughout the 19th century, which began to lose momentum in the early years of the 20th, with the arrival on the scene of schizophrenia (a disease histologically sine materia) in all its epidemiological relevance. The First World War also contributed to the separation between psychiatry and pathology, which unfolded in the fruitless attempts to identify a histopathological justification for the psychological trauma known as shell shock. This condition was defined at the time as a “strange disorder” with very spectacular symptoms (memory loss, trembling, hallucinations, blindness with no apparent organic cause, dysesthesias, myoclonus, bizarre postures, hemiplegia, and more), that may have found neuropathological grounds only some hundred years later. Among the doctors with a passed involvement in the conflict, Ugo Cerletti, the inventor of electroshock treatment, focused on the problem of schizophrenia without abandoning his efforts to identify its organic factors: if inducing a controlled electric shock, just like an experimentallyinduced epileptic seizure, seems to allay the psychotic symptoms and heal the patient, then what happens inside the brain? In seeking histological proof of the clinical effects of electroconvulsive therapy (“the destruction of the pathological synapses”), and attempting to isolate molecules (that he called acroagonins) he believed to be synthesized by neurons exposed to strong electric stimulation, Cerletti extended a hand towards anatomic pathology, and took the first steps towards a neurochemical perspective.